2014
DOI: 10.1007/s12275-014-3601-7
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of recombinant β-glucosidase from Arthrobacter chlorophenolicus and biotransformation of ginsenosides Rb1, Rb2, Rc, and Rd

Abstract: The focus of this study was the cloning, expression, and characterization of recombinant ginsenoside hydrolyzing β-glucosidase from Arthrobacter chlorophenolicus with an ultimate objective to more efficiently bio-transform ginsenosides. The gene bglAch, consisting of 1,260 bp (419 amino acid residues) was cloned and the recombinant enzyme, overexpressed in Escherichia coli BL21 (DE3), was characterized. The GST-fused BglAch was purified using GST·Bind agarose resin and characterized. Under optimal conditions (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…AbpBs activity was weakly affected by β-mercaptoethanol in accordance with concentration, which is well known of thiol group inhibitors. These results suggested that sulfhydryl groups may be involved in the catalytic center of the enzyme [27][28][29]. The enzyme did not require Mg 2+ for activity and was enhanced by 1 mM of Na + , K + , Mg 2+ , Mn 2+ , Ca 2+ , and Co 2+ .…”
Section: Enzyme Characterizationmentioning
confidence: 87%
“…AbpBs activity was weakly affected by β-mercaptoethanol in accordance with concentration, which is well known of thiol group inhibitors. These results suggested that sulfhydryl groups may be involved in the catalytic center of the enzyme [27][28][29]. The enzyme did not require Mg 2+ for activity and was enhanced by 1 mM of Na + , K + , Mg 2+ , Mn 2+ , Ca 2+ , and Co 2+ .…”
Section: Enzyme Characterizationmentioning
confidence: 87%
“…These minor ginsenosides show highly significant pharmacological activities including anti-fatigue, anti-inflammation, anti-neoplastic, anti-fatigue, anti-oxidant and anti-diabetic effects. The enzymatic transformation on these compounds is advantageous as it results in fewer byproducts, better environmental protection and higher stereo-specificity [29].…”
Section: Production Of Enzymes With Biomedical Applications By Arthromentioning
confidence: 99%
“…Many enzymes have been explored to efficiently convert major ginsenosides into pharmacologically active, rare minor ginsenosides [5,13,14]. Prior to this study, our research group cloned, characterized and applied many efficient glycoside hydrolases for the gram-scale production and purification of minor ginsenosides [15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%